Population genetic structure in gadoid fish with focus on Atlantic cod Gadus morhua - Guðni Magnús Eiríksson 1970- (2015)
In the present study genetic variation and population genetic structure in spawning Atlantic cod, Gadus morhua, around Iceland was examined. Earlier research on population genetic structure in cod has not been conclusive and the use of different molecular methods have shown different patterns. It is important to determine why different methods show different patterns in order to describe the population genetic structure in cod. In the present study both microsatellite DNA variation and mitochondrial DNA sequence variation were estimated. Both methods have commonly been used in population genetic studies in cod. Findings of microsatellite DNA variation analysis showed a genetic difference between cod from the waters south and north of Iceland. However, analysis of the observed difference suggest that it can be explained by natural selection affecting genetic variation at a single microsatellite loci (Gmo34). When disregarding this locus from the analysis no genetic difference was observed. Small but significant genetic difference was found among Atlantic cod sampled at different depths off the south coast of Iceland, indicating that different populations of Atlantic cod may be found at different depths. Analysis of mtDNA sequence variation showed no overall genetic difference among different geographic areas around Iceland. Analysis of temporal mtDNA sequence variation showed rapid changes in allele frequencies, particularly in cod from NE-Iceland, suggesting that the mtDNA sequence variation can be useful for detecting recent population divergence. Thus, the findings of the present study do not suggest that cod around Iceland is geographically divided into distinct historical populations as has been suggested in some earlier studies. On the contrary the findings suggest high levels of gene flow in Atlantic cod around Iceland. Genetic variation and population genetic structure across the North Atlantic ocean was also examined in saithe Pollachius virens, haddock Melanogrammus aeglefinus and whiting Merlangius ...